Pengukuran Kualitas Website Unit Pengembangan Karir dan Kewirausahaan Universitas Brawijaya Menggunakan Metode Webqual 4.0 - Ananty Yunanda Rezkiani; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Website is a media technology that can deliver all kinds of information quickly. One of the institutions that use the website media is Unit Pengembangan Karir dan Kewirausahaan Universitas Brawijaya or commonly called UPKK UB. UPKK UB uses website to convey or disseminate information about job vacancy, training and socialization to enter the field of job. UPKK UB said that They never made a measurement of website quality although there are some complaints from the users, so that UPKK UB felt that they need to make a measurement of website qulity.From the description of the problem, the measurement of website quality UPKK UB by using webqual 4.0 method which aim to know webqual variable that influence user satisfaction, from indicator of webqual 4.0 need improvement for website UPKK UB, and give recommendation improvement. Data analysis techniques were performed using SEM (Structural Equation Model). The tool used in this research is SmartPLS 3.0 as a tool (Partial Least Square) PLS. Based on the result of the survey of 99 respondents, the value of R square for the user satisfaction variable is 0.546, which means that the value indicates variable satisfaction can be explained by variable usability, information quality, and service interaction quality of 54.6%, while the rest is 45.4% is influenced by other variables not found in this study. The result of the data analysis there are 7 indicators of webqual 4.0 that need improvement.